Analisis Penggunaan Rupiah Digital dalam Mencegah Risiko Disintermediasi Sistemik pada Bank di Indonesia - Yervant Tavish Serafin Sitompoel; Christine S.T. Kansil (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The Digital Rupiah (Central Bank Digital Currency/CBDC) was designed as a risk-free, publicly accessible Central Bank currency, promising payment system efficiency. However, the presence of the Digital Rupiah creates a structural threat to financial stability through risk disintermediation, namely the large-scale transfer of savings from commercial banks to the Digital Rupiah. This phenomenon has the potential to trigger a very rapid digital bank run, exceeding the mitigation capabilities of existing banking regulations (lex generalis). This study uses a juridical-normative method to analyze the legal landscape arising from the interaction between the Digital Rupiah and the current banking regulatory framework, particularly regarding liquidity protection. The purpose of this study is to provide a reference for new legal instruments to create restrictions. These restrictions serve as preventive legal instruments to ensure the Digital Rupiah functions as a means of payment, not a substitute for commercial bank deposits, thereby ensuring the continuity of the national banking intermediation function. The results of the juridical analysis indicate that the legal instrument of lex generalis banking is unable to address the risk disintermediation of the Digital Rupiah.